To develop values in the first childhood: a proposal of pedagogic action - Paula Maria Santos Koeric; Thais Carboni Martins (Universidade Federal de Santa Catarina, 2008)
In this article we presented the reflections that emerged starting from the children's observation during the apprenticeship accomplished in the Nucleus of Infantile Development (NDI) of the Federal University of Santa Catarina. We looked for to address our glance to the children, privileging the infantile manifestations in your singularities and diversities, in order to we understand your Real desires and needs. For so much, we accomplished observation participativa, in the which we produced written registrations and photographic. Observing the forms as the children links, we noticed the need of we insert in our daily activities with the children the "Values". For that, it was necessary to consider what the children indicated us through your countless expressions, because, it is through the action pedagogic intencionalizada that you/they happen changes in the daily actions, making them if they question on your relationships and they formulate your own judgements on what it is right or wrong.